0
\$\begingroup\$

enter image description here

As shown in the picture above, I want to calculate the voltage drop due to a distributed load.

l is the length of the distributor;

n is simply no of segments, n=l/Δx;

I have written down the sum to determine the voltage drop. But what actually I want to do is to find the "LIMIT OF SUM" of this integral is Δx → 0.

How can I carry out the solution ?

\$\endgroup\$
2
  • 1
    \$\begingroup\$ Why you didn't title your question "Distributed load volt drops" beats me. \$\endgroup\$
    – Andy aka
    Jul 14, 2017 at 15:52
  • \$\begingroup\$ I'm sorry I didn't used that title, because that was not the context of this question. \$\endgroup\$
    – spaul
    Jul 14, 2017 at 16:06

1 Answer 1

1
\$\begingroup\$

I can't say that I feel I completely understood your question. But if I gather it correctly, the value of \$i\$ doesn't change as you move from a finite number of taps to an infinite number of them. This, as you will see, creates a problem that won't be resolvable with a finite answer.

I'm going to label each tap, left to right, as \$k\$ starting with \$k=1\$ on the left and \$k=n\$ at the rightmost tap. You have \$n\$ taps. The current removed at each tap is a constant \$i\$. I'm going to call the entire length, \$L\$ (and not \$l\$.) But the length of each segment of \$L\$ I'll call \$l_k=\frac{L}{n}\$. Length \$L\$ exhibits a certain resistance per unit length \$r\$. The resistance of any segment length is \$r_k=r\cdot l_k=r\frac{L}{n}\$.

The current entering from the left must be the sum of all the branch currents, or \$I=n\cdot i\$. This current must pass through the first segment \$l_1\$ of length \$L\$ and drop a voltage \$v_1=n\cdot i\cdot r\cdot\frac{L}{n}\$. The next segment will drop a voltage \$v_2=\left(n-1\right)\cdot i\cdot r\cdot\frac{L}{n}\$. Etc.

So the question you are asking, "what is the voltage drop across length \$L\$ as \$n\to\infty\$," can be written out this way:

$$\begin{align*} \Delta V=V-V^{'}&= \lim_{n\to\infty} \sum_{k=1}^n \left(n-k+1\right)\cdot i\cdot r\cdot \frac{L}{n}\\\\ &=i\cdot r\cdot L\:\lim_{n\to\infty} \frac{1}{n}\sum_{k=1}^n \left(n-k+1\right)\\\\ &=i\cdot r\cdot L\:\lim_{n\to\infty} \frac{1}{n}\left[\left(n+1\right)\sum_{k=1}^n 1-\sum_{k=1}^n k\right]\\\\ &=i\cdot r\cdot L\:\lim_{n\to\infty} \frac{1}{n}\left[\left(n+1\right)n-\frac{\left(n+1\right)n}{2}\right]\\\\ &=i\cdot r\cdot L\:\lim_{n\to\infty} \left[\frac{1}{n}\frac{\left(n+1\right)n}{2}\right]\\\\ &=i\cdot r\cdot L\:\lim_{n\to\infty} \left[\frac{n+1}{2}\right]\\\\ &=\frac{i\cdot r\cdot L}{2}\:\left[1+\lim_{n\to\infty} n\right] \end{align*}$$

And I don't think I need to tell you how to figure out that limit.


Of course, if you also diminished \$i\$ as a function of \$n\$ then perhaps there might be a different answer. But I didn't see that behavior in your question.

\$\endgroup\$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.